Reduction in Anxiety and Depression Scores Associated with Improvement in Quality of Life in Patients with Inflammatory Bowel Disease. Issue 1 (19th May 2021) - Farbod, Yasamin; Popov, Jelena; Armstrong, David; Halder, Smita; Marshall, John K; Tse, Frances; Pinto-Sanchez, Maria Ines; Moayyedi, Paul; Chauhan, Usha
Abstract: Background: The aim of this study was to examine the associations among depression, anxiety and health-related quality of life and predictors of improvement of quality of life in patients with inflammatory bowel disease. Methods: This was a prospective cohort study conducted in the gastroenterology clinic at McMaster University Medical Center in Hamilton, Ontario, Canada from May 2014 to March 2015. We included 60 adult patients above the age of 18 years old with a diagnosis of inflammatory bowel disease. We assessed anxiety and depression using the Hospital Anxiety and Depression Scale (HADS) and Health Related Quality of Life (HRQoL) using the Short Inflammatory Bowel Disease questionnaire (SIBDQ) at baseline and after 6 months. Linear regression was performed to estimate the associations among depression, anxiety and predictors of improvement in health-related quality of life. Results: The anxiety scores decreased over the span of 6 months (median HADS-A baseline 9.00 [interquartile range IQR 6 to 12], and median HADS-A 6 months 7.00 [IQR 3.75 to 7.00]). There was a moderate negative correlation between anxiety (baseline r = −0.510, and 6-month r = −0.620; P < 0.001), depression (baseline r = −0.630, and 6-month r = −0.670; P < 0.001) and HRQoL scores. Using a multivariate linear regression model, elevated HADS score were associated with lower SIBDQ scores at baseline (Beta coefficient −0.696 [95% confidence interval CI −1.51 to −0.842]; P < 0.001). Lower SIBDQ score at baseline predicted decreased SIBDQ at 6 months (Beta coefficient 0.712 [95% CI 0.486 to 1.02]; P < 0.001). Conclusion: Anxiety and depression are frequently seen in inflammatory bowel disease patients and lead to poor HRQoL. Psychological comorbidities may contribute to maladaptive behaviours and difficult disease management.